Dividend policy and market value of banks in MENA emerging markets: Residual income approach - Akram Ramadan Budagaga (Journal of Capital Markets Studies (JCMS), 2020)
Purpose This study will examine the impact of cash dividends on the market value of banks listed in Middle East and North African (MENA) emerging countries during the period 2000-2015. Design/methodology/approach The current study adopts residual income approach based on Ohlson's (1995) valuation model. By testing different statistical techniques, fixed effect is applied on panel data for (144) banks listed on 11 MENA stock markets over the period 2000-2015. Furthermore, additional tests are applied to confirm the primary results. Findings The analysis reveals that current dividend payouts and dividend yield do not provide information relevant to the establishment of market values in MENA emerging markets; thus, they have no material impact on MENA banks' market values. This lack of current dividend payment effect is consistent with Miller and Modigliani (1961) dividend irrelevance assumption: there is no evidence of either an informational or real cash inflow effect of current dividend payments. The findings of this study can be attributed to the fact that MENA banks may be forced to place more emphasis on allocating money for investment instead of paying dividends given them they are subject to liquidity requirements for investment, expansion, general operations and compliance with regulations. Only after all these financial needs are covered can the remaining surplus be distributed as cash dividends. Therefore, cash dividends represent earnings residual rather than an active decision variable that impacts a firm's market value. This is consistent with the residual dividend hypothesis, which is the crux of Miller and Modigliani (1996) irrelevance theory of dividends. Research limitations/implications The current study is restricted to a sample of one type of financial firms, banks, because of the problem of missing data and limited information related to other financial firms for the same period. Therefore, further research could be additional types of financial firms such as insurance firms that play a vital role in MENA emerging economies. Practical implications The results of this study have some important implications for banks' dividend policymakers. Dividend policymakers in MENA emerging markets seem to follow residual dividend policy, in which they distribute dividends according to what is left over after all acceptable investment opportunities have been undertaken. This makes for inconsistent and unstable dividend policy trends, making it difficult for investors to predict future dividend decisions. Further, this practice may deliver information to shareholders about a lack of positive future investment opportunities, and this may negatively affect the share value of banks. Originality/value This study is the first of its kind - up to the author's knowledge - that examines a large cross-country sample of MENA banks (144) to cover a long time period in the recent past, and, more importantly, after the banking sector in the region has experienced major transformations during last two decades. In addition, most of the MENA region countries included in this study, namely, banks, operate in tax-free environments (there are neither taxes on dividends nor on capital gains). This feature adds complexity to the ongoing dividend debate.
Keywords: 330; Banks; Dividend policy; Market value; MENA markets; Residual income model